(untitled) (Global Journal of Human-Social Science, 2020)
Transgender people are those who have a gender identity or gender expression that is at variance from their perceived sex. Being transgender is autonomous of sexual orientation. The degree to which the individual feels real, authentic and at ease with their outward manifestation and acknowledge their actual identity has been called transgender congruence. Most transgender people are prejudiced in their place of work and denied access to public spaces and healthcare. In many places, they do not even get any legal remedy against prejudice and intolerance. This paper is an attempt to deconstruct heteronormative default paradigms on sexuality and sexual orientation. It also looks into the practice and consequence of how this reign of heteronormativity hijacks and distorts the life of transgender people in India. A. Revathi’s life narrative, The Truth about Me: A Hijra Life Story is a good case in point. This narrative evidently illustrates the ways in which a typical heteronormative, prescriptive as well as patriarchal society enforces restrictions on the sartorial, vocational and economic proclivities of a set of people called hijras. It is a painful account of distress and disappointment, but the goal is not to solicit commiseration or favours from society or administration; on the contrary, to carve out a little space for this particular group in the gender firmament, thereby informing the world that they too want to lead a life!.